OH INCORPORATION IN SYNTHETIC DIOPSIDE - Stalder R.; Ludwig T. (My University, 2007)
Single crystals of diopside doped with different amounts of Fe, Cr, Al and Na were synthesized under silica- and water-saturated conditions at 20 kbar. The OH-incorporation was studied by FTIR-spectroscopy and secondary ion mass spectrometry. Pure diopside exhibits one OH-absorption band at 3357 cm -1, whereas additional absorption bands appear for AI-, Fe- and Cr-doped diopsides at 3462, 3443 and 3432 cm-1, respectively. The observed absorption bands are interpreted to be associated with M-site vacancies, and the absence of high wavenumber absorption bands is suggested to be diagnostic for a high silica activity. Incorporation of Na in a Cr-doped diopside caused a decrease of OH-defects, consistent with a simple increase of the kosmochlor component. © 2007 E. Schweizerbart'sche Verlagsbuchhandlung.
Keywords: CLINOPYROXENE; HIGH PRESSURE; IR-SPECTROSCOPY; OH INCORPORATION; SIMS